Appropriate lifetimes, fitting deaths. Issue 23 (1st November 2016) - Scott, Janet L.; Lee, Jacquetta
Abstract : Editorial on the principle that "Chemical products should be designed so that at the end of their function they do not persist in the environment and break down into innocuous degradation products".